Recent trends in substation automation and enterprise data management - McDonald, John D. (IEEE, 2010)
The purpose of this tutorial is to familiarize participants with all aspects of substation automation for both electric utility and industrial applications. The term Intelligent Electronic Device (IED) is defined. The different levels of substation integration and automation are discussed. The reasons a utility or industrial facility would need substation automation are presented. The components of the integration and automation architecture are discussed with respect to their technical issues. This discussion flushes out the sensitive, controversial issues that need to be addressed by a utility or industrial facility when implementing substation automation. The characteristics and interface issues associated with Intelligent Electronic Devices (IEDs) are addressed, since the integration architecture is only as good as the integration capabilities of the IEDs themselves. Communication protocol fundamentals and considerations are discussed. Relevant industry standards and their impact on substation automation are described. The characteristics of extracting the valuable data from substation Intelligent Electronic Devices (IEDs) and effectively managing this data in the electric utility or industrial facility enterprise is illustrated
Description based on online resource; title from title screen (IEEE Xplore Digital Library, viewed November 12, 2020)
Keywords: Automation; Intelligent Manufacturing Systems; Film